2017
DOI: 10.1007/s10856-017-5966-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite particles with improved microstructure for 3D culture systems and bone regeneration

Abstract: Nano-apatite and gelatin-alginate hydrogel microparticles have been prepared by a one-step synthesis combined with electrostatic bead generation, for the reconstruction of bone defects. Based on the analysis of bone composition, architecture and embryonic intramembranous ossification, a bio-inspired fabrication has been developed. Accordingly, the mineral phase has been in situ synthesized, calcifying the hydrogel matrix while the latter was crosslinked, finally generating microparticles that can assemble into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The micrograph in Figure 7o presents the morphological details specific to nanoapatite crystals intimately combined with the organic matrix. We previously described similar morphology consisting in bundles of rod-like nanocrystallites generating a porous nanocomposite structure [27]. Such morphology suggested that the mineral was formed following intense and homogeneous Ca/P capturing by the hydrogel, followed by precipitation.…”
Section: Casein Effect On the Mineralisation Of The Hybridsmentioning
confidence: 76%
“…The micrograph in Figure 7o presents the morphological details specific to nanoapatite crystals intimately combined with the organic matrix. We previously described similar morphology consisting in bundles of rod-like nanocrystallites generating a porous nanocomposite structure [27]. Such morphology suggested that the mineral was formed following intense and homogeneous Ca/P capturing by the hydrogel, followed by precipitation.…”
Section: Casein Effect On the Mineralisation Of The Hybridsmentioning
confidence: 76%
“…With tight control over the instantaneous magnitude release rate, pulsatile release patterns may be created. [ 45 ]…”
Section: Physicochemical Properties Of Hydrogelsmentioning
confidence: 99%
“…As opposed to other techniques, CT provides a general overview of either dried or hydrated samples, thus increasing its importance in scaffold characterization for biomedical applications. Despite this significant advantage, only a relatively small number of papers report the evaluation in hydrated state [69][70][71][72] due to the difficulty of obtaining a good X-ray contrast between the hydrated matrix and immersion media.…”
Section: Visualization Of Architectural Features Through Ct Imagingmentioning
confidence: 99%